Multifamily Group Intervention for Chinese Parents and Their Children with Attention Deficit Hyperactivity Disorder in a Chinese Context. Issue 3 (3rd July 2017) - Ma, Joyce L. C.; Lai, Kelly Y. C.; Wan, Erica S. F.
ABSTRACT: Despite the empirical evidence of multifamily group (MFG) in helping children with mental health needs in Western contexts, there is a dearth of clinical studies in Chinese societies such as Hong Kong to explore such adaption to help Chinese families of children diagnosed with attention deficit hyperactivity disorder. In this article, the authors describe the MFG model adapted to the Chinese context and assess the perceived helpfulness of the intervention, using a client-driven approach in evaluation. The parents' evaluation toward the MFG program is positive whereas the children's feedback is less favorable. Modifications have been made including a 30-minute pregroup meeting for the parents and more challenging games and outdoor activities for the children.